IDENTIFIKASI AWAL SITUS MASA KLASIK DI LEUWILIANG KABUPATEN BOGOR - Rusyanti, Rusyanti (PANALUNGTIK, 2019)
Bogor is a location that belongs to the influence of the Sunda kingdom in the past. This area is often found the remains of the past that are suspected as archaeological artifacts, one of which is a report of urns findings in the  Barengkok village in Leuwiliang District, Bogor Regency. To confirm the findings, the West Java Archaeological center conducted preliminary research and field surveys. The results indicated that the findings of the objects inside the jar are of ceramic fragments, pottery and metals allegedly were collectible items that were deliberately placed in a jar and then buried,  the burial purpose is yet unknown because the remains are not associated with other findings although the location of the findings still has a chance to contain archeological potential since the  classical  sites in Indonesia is often adjacent to the river, on high land and or elevated and oriented to mountains or high places. Advanced research and test pit is a preliminary recommendation that can be done at a later stage.